Marketing Impact of Halal Labeling toward Indonesian Muslim Consumer’s Behavioral Intention Based on Ajzen’s Planned Behavior Theory: Policy Capturing Studies on Five Different Product Categories - Salehudin, Imam; Luthfi, Bagus Adi (UI Scholars Hub, 2021)
The purpose of this paper is to test the applicability of the theory of planned behavior (TPB) in explaining the intention to switch from products without certified Halal labels within a wide array of purchase context, especially in the purchase of food and medicine products. A policy capturing questionnaire was used to elicit responses from consumers using a convenience sampling technique. A total of 7500 responses were obtained from 150 participating respondent in 50 different scenario cases. Data is analyzed using Multi-Group Structural Equation Modeling. The study finds that the Theory of Planned Behavior (TPB) is not completely valid to explain both the behavioral intention of Muslim consumers in Indonesia to seek information about the Halal certification of a product and to cancel their purchase if the product did not have Halal certification. Differences in magnitude and significance of causal relationships exist between different product categories.